Design of Stretching Equipment for the Elderly - Rotsakunphanit, Chumsit; Rungfa, Yingyong; Utchariyamedhakorn, Pornchai; Siraphatthada, Yananda; Parmotmuang, Mattanee (Rajamangala University of Technology Tawan-ok Research Journal, 2024)
The experimental research of the designing of a standing stretching device for the elderly aims to study various equipment used for stretching for the health of the elderly and to develop a standing stretching device for the elderly. The satisfaction with the design of the standing stretching device for the elderly was evaluated by occupational therapists and design experts. The scope of the research included studying the criteria for designing a standing stretching device for the elderly. The sample group consisted of elderly males and females aged 60 and above. The research instruments included interviews with occupational therapists, interviews with design experts, and satisfaction surveys regarding the design. The research results show that the overall design of the standing stretching device for the elderly has dimensions of 500 millimeters in width, 750 millimeters in length, and 750 millimeters in height at the supporting part. The material used for production was hollow round steel with a diameter of 20 millimeters. The components included a standing board made of 16-millimeter thick plywood, with dimensions of 430 millimeters in width and 470 millimeters in length, covered with a non-slip rubber sheet. The materials used for the front and side components were injection-molded plastic. The design of the standing stretching device allows for adjustable tilt angles using a mechanical system and a 12V DC motor, with a control device installed on both handles for ease of use and suitability for the physical condition of the elderly. The satisfaction with the design was found to be at a very satisfactory level.